Opportunities to Prevent Alcoholic Liver Cirrhosis in High-Risk Populations: A Systematic Review With Meta-Analysis. (February 2019) - Askgaard, Gro; Kjær, Mette S.; Tolstrup, Janne S.
Abstract : BACKGROUND: Alcoholic liver cirrhosis is preventable and caused by heavy drinking. Few in the general population may be at risk and interventions targeting individuals at high risk may be a more feasible opportunity for prevention than interventions targeting the whole population. METHODS: We conducted a systematic review to identify opportunities to prevent alcoholic liver cirrhosis in high-risk populations. Following MOOSE guidelines, we included observational studies published between 1980 and 2017. Prospective studies of alcohol-problem cohorts were included to investigate whether alcohol-problem cohorts qualify as high-risk populations for alcoholic liver cirrhosis. Studies on the alcohol amount consumed by alcoholic liver cirrhosis patients were included to compare with the amount consumed by the general population. Moreover, studies on alcohol-related healthcare contacts prior to alcoholic liver cirrhosis diagnosis were included to identify opportunities to offer prevention interventions. Of 7198 screened references, 38 studies ( N = 120, 928) were included. RESULTS: Alcohol-problem cohorts qualified as high-risk populations with an incidence of alcoholic liver cirrhosis ranging from 7 to 16% after 8–12 years. The alcohol amount consumed by alcoholic liver cirrhosis patients was high compared to the general population. For example, 45% (95%CI 34, 56) of alcoholic liver cirrhosis patients were drinking >110 g alcohol/day. Finally, there were opportunities to reach alcoholic liver cirrhosis patients prior to diagnosis; 40–61% of alcoholic liver cirrhosis patients had a previous alcohol-related healthcare contact. CONCLUSIONS: We conclude that alcohol-problem cohorts are high-risk populations for alcoholic liver cirrhosis and there seems to be opportunities to reach later alcoholic liver cirrhosis cases with preventive interventions in healthcare settings.